Method for preparing ultra-wide-spectrum and ultra-high-absorption aluminum plane black body by using inert gas to assist femtosecond laser
By using inert gas assisted femtosecond laser processing on the surface of aluminum alloy, a conical pointed micro-nano composite structure with a high aspect ratio was prepared, which solved the problems of insufficient wide spectrum light absorption capacity and plasma shielding effect in the prior art, and achieved ultra-high absorption performance and stability within the ultra-wide spectrum range.
Patent Information
- Application Number
- CN202510035101.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The prior art methods to achieve high electromagnetic absorption on the surface of aluminum alloys have problems such as insufficient wide spectrum light absorption capacity, possible environmental pollution in the coating preparation process, poor stability, and insufficient sharpness on the top of the micro-nano composite structure caused by plasma shielding effects, and cannot achieve ultra-high absorption performance of the ultra-wide spectrum.
Inert gas (such as nitrogen or argon) assisted femtosecond laser processing is used to suppress the plasma shielding effect, and a conical micro-nano composite structure with a high aspect ratio is prepared. By optimizing the geometric light-catching effect of the microstructure and the dielectric effect of the nano-oxidation layer, high absorption rate within the ultra-wide spectrum range is achieved.
It realizes an aluminum alloy planar bold with light absorption of more than 98.5% in the ultraviolet to long-wave infrared range, with excellent high and low temperature stability and mechanical friction stability, and is suitable for infrared calibration, passive radiation cooling and stray light suppression and other applications.
Smart Images

Figure CN119820080A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser micro-nano processing, and specifically relates to a method for preparing an ultra-wide spectrum and ultra-high absorption aluminum alloy plane black body by utilizing an inert gas-assisted femtosecond laser. Background Art
[0002] The control of electromagnetic absorption properties is an important topic in the field of materials science and surface engineering. The ability to design surfaces with near-perfect high electromagnetic absorption over a wide spectrum has attracted great interest due to its potential applications in various fields such as photonics, optoelectronics, and thermal radiation. Aluminum alloy has the advantages of high thermal conductivity and light weight, and is one of the most widely used infrared calibration flat blackbody materials after black treatment. However, due to the huge optical impedance mismatch between aluminum alloy and free space, current aluminum alloy flat blackbodies usually show poor, narrow-band, non-uniform and unstable absorption. The techniques for achieving high electromagnetic absorption on aluminum alloy surfaces can be simply divided into two categories:
[0003] 1. Coating method: The coating method refers to coating a high-absorption coating on a substrate, and using the intrinsic high absorption of the coating to achieve high absorption of the substrate. This method has many advantages, including simple use and wide applicability; but it also has inevitable disadvantages, that is, the ability to absorb broad-spectrum light is usually poor, and there may be environmental pollution problems in the coating preparation process, and stability is a big problem, and it is very easy to lose its effect in harsh environments such as space;
[0004] 2. Surface microstructure method;
[0005] Surface microstructure methods include dry etching represented by photolithography and laser ablation represented by femtosecond laser processing. The dry etching method can accurately define the microstructure and nanostructure of the surface, and theoretical work has demonstrated adjustable and near-perfect light absorption within the designed wavelength range. However, since the absorptivity of this method depends on the precisely defined microstructure and nanostructure, it is impossible to achieve high absorption within a wide spectrum range, and the preparation process is relatively complex and expensive, and it is not suitable for processing large-area planar black bodies. The laser ablation method can obtain cross-scale, multi-level micro-nano composite structures, and has achieved relatively high anti-reflection effects in some wide spectrum ranges, providing a basis for the realization of an ideal black body. However, due to the plasma shielding effect during the processing of the structural aluminum alloy plane black body (when the femtosecond laser directly scans the aluminum alloy surface in an air environment, the huge energy at the focus will ionize the aluminum alloy substrate and the surrounding air. This leads to the formation of a redeposition plasma composed of elemental aluminum and oxygen, which hinders the interaction between the subsequent laser pulse and the substrate material), the top of the micro-nano composite structure on the aluminum alloy surface is not sharp enough, the first reflection of the incident electromagnetic wave is too high, and a high aspect ratio micro-nano composite structure cannot be achieved, which ultimately leads to poor light absorption performance in the short-wave infrared region and the inability to achieve ultra-high absorption performance in an ultra-wide spectrum (from ultraviolet to long-wave infrared band). Summary of the invention
[0006] In the prior art, femtosecond laser processing is directly used in an air environment, and the resulting micro-nano composite structure usually has an elliptical shape, and the surface is covered with a thick layer of aluminum oxide nanoparticles. This elliptical structure is limited in achieving a higher aspect ratio. In order to solve the problem of elliptical structure caused by plasma shielding effect in traditional laser processing methods, the present invention provides a method for preparing an ultra-wide spectrum and ultra-high absorption aluminum alloy planar black body using inert gas assisted femtosecond laser. The method is to adjust the background gas used in the femtosecond laser processing process to an inert gas. In an inert gas environment, the plasma shielding effect in the laser processing process is suppressed, so the corresponding cone-shaped micro-nano composite structure has a higher aspect ratio and a sharper cone tip; the primary reflection of the cone-shaped micro-nano composite structure is very small, ensuring that the incident electromagnetic wave can all enter the gap between adjacent cone-shaped micro-nano composite structures and be absorbed layer by layer through multiple internal reflections. The typical structural feature prepared by the present invention is a cone-shaped micro-nano composite structure. By optimizing the geometric light-trapping effect of the micron structure, as well as the effective dielectric effect and resonant light absorption of the nano-oxide layer and the nitride layer, an aluminum alloy plane black body with a light absorption of more than 98.5% in the ultraviolet to long-wave infrared range (0.2-25μm) is prepared. In addition, the prepared aluminum alloy plane black body exhibits excellent high and low temperature stability and mechanical friction stability, and has important application potential in infrared calibration, passive radiation cooling and stray light suppression.
[0007] The present invention is achieved through the following technical solutions:
[0008] The method for preparing an ultra-wide spectrum and ultra-high absorption aluminum alloy planar black body by using an inert gas-assisted femtosecond laser specifically comprises the following steps:
[0009] Step 1: Processing of samples to be processed;
[0010] The aluminum alloy sample to be processed is placed in a sealed polytetrafluoroethylene beaker with acetone solution, taken out after ultrasonic cleaning, rinsed with ethanol and deionized water in turn, and placed in a low-temperature oven for drying; then the aluminum alloy sample is taken out for use, and the sample preparation is completed;
[0011] Step 2: Processing aluminum alloy samples by femtosecond laser in an inert gas environment;
[0012] First, the sample is placed in a transparent box that can pass inert gas. The box is fixed on a two-dimensional mobile platform to meet the precise movement of the sample in the XY plane. The femtosecond laser emitted by the femtosecond laser enters the three-dimensional galvanometer processing system focused by the field lens after beam expansion. The galvanometer of the three-dimensional galvanometer processing system is installed on a z-axis displacement stage that can move up and down. The femtosecond laser deflected by the galvanometer is then focused on the upper surface of the sample through the field lens. Then, the switch of the gas cylinder containing inert gas is turned on to pass inert gas into the transparent box. Finally, the z-axis is adjusted to make the laser focus on the upper surface of the sample, and the pre-designed processing file is read into the processing program. The direct writing processing is performed by scanning back and forth row by row on the x-axis and then scanning back and forth column by column on the y-axis. Finally, a conical micro-nano composite structure with a high aspect ratio can be prepared.
[0013] Step 3: ultrasonic treatment of metal samples;
[0014] The sample obtained in step 2 is ultrasonically cleaned to remove the debris remaining after processing and retain the stable cone-shaped micro-nano composite structure. It is then dried in a dryer or blown dry with an ear bulb. At this point, the aluminum alloy sample with ultra-wide spectrum and ultra-high absorption rate is prepared.
[0015] Furthermore, in step one, the material of the aluminum alloy sample to be processed is not limited to a single aluminum alloy, but should include various softer aluminum alloys, such as 6061 aluminum alloy, and other softer metal materials, such as magnesium alloy, tin, lead, etc.; the size of the aluminum alloy sample is 3cm-10cm, the thickness is 1mm-10mm, the polytetrafluoroethylene beaker is sealed in the fume hood for ultrasound to prevent the acetone solution from volatilizing, the ultrasound time is 0.1h-2h, and the low-temperature oven temperature is set to 50℃-100℃.
[0016] Furthermore, in step 2, the transparent box for inert gas can be made of acrylic plate or other transparent material that allows laser to pass through, providing an inert gas environment for the sample during processing. If it is replaced with a box, glove box, etc. made of other materials, the effect is similar. There is a circular hole on each side of the transparent box, which is connected to an air pipe for the inert gas to flow in and out, and the flow rate of the inert gas is 0.1-10L / min.
[0017] Furthermore, in step 2, the inert gas is nitrogen or argon.
[0018] Furthermore, in step 2, the moving range of the x-axis and y-axis of the two-dimensional moving platform is 0-10cm, the moving range of the z-axis translation stage is 0-10cm, and the accuracy is 1μm; the galvanometer used in the three-dimensional galvanometer processing system is composed of an XY optical scanning head, an electronic drive amplifier and an optical reflective lens. The signal provided by the computer controller is sent to the electronic drive amplifier, and the electronic drive amplifier is used to drive the XY optical scanning head, thereby controlling the high-speed deflection of the laser beam in the XY plane, and the moving accuracy is 10-100nm; the laser polarized by the galvanometer is then focused on the sample surface through the field lens to realize femtosecond laser direct writing processing.
[0019] Furthermore, in step 2, the fundamental wavelength of the femtosecond laser is 1030nm, and after double frequency, the wavelength becomes 515nm, which is a femtosecond laser in the visible region; or after triple frequency, a near-ultraviolet femtosecond laser or nanosecond laser, or picosecond laser of 343nm is obtained; the repetition frequency of the laser is 50kHz-1000kHz, and the pulse width is 280fs; the focal length of the focusing field lens used is 5-20cm, which meets the requirements of large-area processing, and even the required conical micro-nano composite structure can be prepared by focusing with an objective lens or a lens; the single pulse energy of laser ablation is 1-100μJ, and the laser scanning speed is 1-1000mm / s, which meets the requirements of high-speed processing; the point spacing of the processing data is 50-10000nm, the period is 10-100μm, the layer spacing is 1-30μm, and the number of scans is 1-100 times.
[0020] Furthermore, in step three, the ultrasonic cleaning time is 0.1h-2h; the solution used for ultrasonic cleaning is deionized water or ethanol, which can remove debris that is not firmly bonded to the surface of the cone-shaped micro-nano composite structure.
[0021] On the other hand, the present invention also provides an ultra-wide spectrum, ultra-high absorption aluminum alloy planar black body, which is prepared by the above method, and the aluminum alloy planar black body has an anti-reflection structure with adjustable period and aspect ratio, and the anti-reflection structure is a cone-shaped micro-nano composite structure, and the tip angle of the cone-shaped micro-nano composite structure is less than 10°.
[0022] Furthermore, the cone-shaped micro-nano composite structure includes a micron cone-shaped structure layer, an oxide layer and a nanoparticle layer.
[0023] Furthermore, the cone-shaped micro-nano composite structure can achieve an absorption rate of more than 98.5% in the range of 200nm-25μm.
[0024] Compared with the prior art, the advantages of the present invention are as follows:
[0025] (1) Compared with the surface coating method, both methods are relatively simple, but the surface structure processed by femtosecond laser has stability that the coating method does not have, will not decompose over time, and is environmentally friendly. The coating method is generally targeted at a specific band, while the surface structure of the present invention is targeted at an ultra-wide spectrum region;
[0026] (2) Compared with other surface microstructure methods, the advantage of the present invention is that it can prepare a conical micro-nano composite structure with a high aspect ratio on the surface of aluminum alloy, and can achieve ultra-high uniform absorption rate in an ultra-wide spectrum range. Dry etching methods such as photolithography have precisely designed geometric structures and use the resonant light absorption mechanism to obtain ultra-low surface reflectivity, but the absorption spectrum range strongly depends on the period and size of its component structure, is limited to a narrow and specific wavelength range, and the preparation process is complicated; the traditional laser ablation method has the problem of excessive plasma shielding effect when preparing micro-nano structures on the surface of aluminum alloy, resulting in poor absorption rate in the near-infrared region, and ultimately unable to achieve ultra-high absorption rate in the ultraviolet-long-wave infrared region.
[0027] (3) The present invention utilizes the ultrashort pulses and extremely high peak power of a femtosecond laser in an inert gas environment to ablate and remove materials, thereby preparing a conical tip micro-nano composite structure with a high aspect ratio on the surface of the aluminum alloy, thereby achieving a high absorption rate of more than 98.5% in the range of 200nm-25μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the specific embodiments or the description of the prior art. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.
[0029] Figure 1 Schematic diagram of plasma shielding effect when processing aluminum alloy in air environment and nitrogen environment;
[0030] Among them, a is air environment, b is nitrogen environment;
[0031] Figure 2 The schematic diagram and comparison of processing results in air environment and nitrogen environment;
[0032] Among them, a and b are the processing schematic diagrams in air environment and the elliptical micro-nano composite structure respectively;
[0033] cd are the processing schematic diagram under nitrogen environment and the cone-shaped micro-nano composite structure;
[0034] Figure 3 The electron microscope image, cross-sectional curve graph and absorption rate test result schematic diagram of the present invention for regulating the cone-shaped micro-nano composite structure with different periods and depths;
[0035] Among them, ac are electron microscope images of structures with the same period but different depths, the period is 50μm, and the depths are 130μm, 170μm, and 210μm respectively, d is the corresponding cross-sectional curve graph, and e is the corresponding absorption rate test result;
[0036] fh are electron microscope images of structures with different periods at the same depth, the depth is 170μm, and the periods are 40μm, 50μm, and 60μm, respectively; i is the corresponding cross-sectional curve graph, and j is the corresponding absorption rate test result;
[0037] Figure 4 This is a cross-sectional electron microscope image of a high aspect ratio conical tip micro-nano composite structure with a cone angle less than 10°;
[0038] Figure 5 The physical image, electron microscope image, three-dimensional confocal image, cross-sectional curve graph and schematic diagram of absorptivity test results of the large-area aluminum alloy plane black body prepared by the present invention;
[0039] Among them, a is the physical image, bc is the electron microscope image, ef is the three-dimensional confocal image and cross-sectional curve, and g is the absorbance test result;
[0040] Figure 6 Schematic diagram comparing the absorption rate results of samples under three background gas environments when the laser processing parameters and gas flow rate are the same. DETAILED DESCRIPTION
[0041] In order to clearly and completely describe the technical solution and its specific working process of the present invention, the specific implementation methods of the present invention are as follows in conjunction with the accompanying drawings of the specification:
[0042] Example 1
[0043] This embodiment provides a method for preparing cone-shaped micro-nano composite structures of different periods and depths by using nitrogen-assisted femtosecond laser processing, and the specific steps are as follows:
[0044] (1) Processing of samples to be processed;
[0045] First, the aluminum alloy sample to be processed is placed in a sealed polytetrafluoroethylene beaker with acetone solution and ultrasonically cleaned for 1 hour, then taken out, and then cleaned with ethanol and deionized water in turn, and a cotton ball dipped in the corresponding solution is grasped with tweezers to wipe in the same direction. During the wiping process, be careful not to leave scratches on the sample surface with the tweezers, and then the sample is placed in a 50℃ low-temperature oven for drying; then the aluminum alloy sample is taken out for use, and the sample preparation is completed;
[0046] (2) Processing aluminum alloy samples by femtosecond laser in a nitrogen environment;
[0047] First, fix the sample to the bottom of a transparent acrylic box with traceless glue, then fix the box on a two-dimensional mobile platform, insert a nitrogen tube, and adjust the nitrogen flow rate to 1L / min. Adjust the z-axis so that the laser focuses on the upper surface of the sample; then read the pre-designed processing file into the processing program, and perform direct writing processing by scanning back and forth row by row on the x-axis and then scanning back and forth column by column on the y-axis; the single pulse energy of laser ablation is 20μJ, the laser scanning speed is 10mm / s, the point spacing of laser scanning is 5μm, the layer spacing of laser scanning is 10μm, the laser scanning cycle is 40μm, 50μm, 60μm, and the number of laser scans is 5 times, 10 times, and 15 times.
[0048] like Figure 1 As shown in a, when processing in an air environment, for some soft metal materials, such as 6061 aluminum alloy, the plasma shielding effect during the processing will be more serious. Because the ionization energy of aluminum is relatively small, only more than 500 kJ / mol, it is easily ionized. For harder metal materials, such as iron and copper, the ionization energy is relatively large, reaching more than 700 kJ / mol, so it is not easy to be ionized during the processing, and the plasma shielding effect is relatively small. In short, due to the huge energy at the focus of the femtosecond laser, the aluminum alloy and the air will be ionized to form a large amount of plasma, which will hinder the subsequent interaction between the laser energy and the aluminum alloy. Figure 1 As shown in b, the background gas is changed to nitrogen. Since nitrogen is an inert gas and is less likely to be ionized, the amount of plasma generated will be greatly reduced, which is beneficial to the preparation of high aspect ratio cone-shaped micro-nano composite structures on the surface of aluminum alloy.
[0049] Figure 2 The schematic diagram of the preparation process under two gas environments is given. The micro-nano composite structure obtained under air environment usually has an elliptical shape due to the large plasma shielding effect, and the surface is covered with a thick layer of aluminum oxide nanoparticles ( Figure 2 A and Figure 2b). The top of this elliptical structure is not sharp enough, which is not conducive to reducing the primary reflection of the incident electromagnetic wave. Moreover, the laser energy cannot continue to penetrate deep into the structure and cannot achieve a higher aspect ratio, which is not conducive to its geometric light capture ability. In addition, although the thick aluminum oxide nanoparticles can form nano absorption centers due to their characteristic absorption band (10-25μm), which can increase the light absorption of the elliptical micro-nano composite structure in the mid-wave infrared to long-wave infrared region, the absorption in the mid-wave infrared to short-wave infrared region is poor due to the inability to achieve a high aspect ratio cone-shaped micro-nano composite structure.
[0050] like Figure 2 C and Figure 2 As shown in d, the typical structural feature of the micro-nano composite structure prepared in a nitrogen environment is a high aspect ratio cone-shaped micro-nano composite structure covered with a thin layer of a mixture of aluminum oxide and aluminum nitride. Since a sharper cone-shaped micro-nano composite structure with a higher aspect ratio can be processed in a nitrogen environment, by optimizing the geometric light-trapping effect of the microstructure, as well as the effective dielectric effect and resonant light absorption of the nano-oxide layer and the nitride layer, an aluminum alloy plane black body with ultra-high absorptivity in an ultra-wide spectrum range can be prepared. The inherent mechanism for preparing a cone-shaped micro-nano composite structure in a nitrogen environment is that the nitrogen atmosphere suppresses the plasma shielding effect during the processing, the amount of plasma generated is small, and the amount of redeposited plasma is also small, so the effect of laser ablation removal in this process is more obvious, which is more conducive to the realization of a cone-shaped micro-nano composite structure. In addition, the less plasma in this process also scatters less incident laser light, and the laser energy can penetrate deeper into the structure, so the preparation of a cone-shaped micro-nano composite structure with a high aspect ratio can be achieved.
[0051] The inert gas background in step (2) can be replaced with other inert gases that have better plasma shielding effect, such as argon. Argon atmosphere has a better effect of suppressing plasma shielding effect, but it will reduce the thickness of the oxide layer on the surface of the cone-shaped micro-nano composite structure and the complexity of the nanoparticle structure, which is not conducive to further improving the absorption rate. However, if the purpose is to prepare a high aspect ratio cone-shaped micro-nano composite structure, replacing the background gas with argon or other inert gases may have a better effect.
[0052] (3) Ultrasonic chip removal of aluminum alloy samples;
[0053] The sample obtained in step (2) is placed in deionized water for ultrasonic cleaning for 1 hour to clean the debris remaining after processing, leaving only the micro-cones and nano-particle structures that can exist stably, and then dried in a dryer or blown dry with an ear bulb. At this point, the preparation of the aluminum alloy sample with ultra-wide spectrum and high absorption rate is completed.
[0054] (4) Characterization and absorption rate test of cone-shaped micro-nano composite structures with different periods and depths;
[0055] The equipment used for the absorbance test is a VERTEX 70 Fourier infrared spectrometer with an integrating sphere and a UV3600 with an integrating sphere. Since the integrating sphere test has requirements on the sample size, a sample with a length and width greater than or equal to 2 cm is prepared by the method described in this embodiment for testing. The finally prepared high-absorption aluminum alloy sample is placed close to the dedicated integrating sphere, and then the diffuse reflectance at 200nm-25μm is tested using a Fourier infrared spectrometer and UV 3600, and then the absorbance is obtained according to 1-diffuse reflectance.
[0056] Figure 3 The results show that nitrogen-assisted femtosecond laser processing can prepare cone-shaped micro-nano composite structures with different periods and widths, and the test results of their absorption rate show that when the period is 50μm and the depth is 170μm (sample B), the aluminum alloy plane black body has the highest light absorption rate due to the synergistic effect of the various parts of the micro-nano composite structure. When the depth is reduced or increased (samples A and C), or the period is reduced or increased (samples D and E), the absorption rate is not as good as the structure with a period of 50μm and a depth of 170μm.
[0057] Figure 4 The structure with the highest aspect ratio prepared at a period of 50μm is shown, with a depth of 286μm. The high aspect ratio cone-shaped micro-nano composite structure processed in a nitrogen environment should have a small enough angle of less than 10° to ensure that the electromagnetic wave is confined to the gap between adjacent cone-shaped micro-nano composite structures after incidence. Using a triangle to fit, assuming that the period of the prepared cone-shaped micro-nano composite structure is x and the depth is y, the angle is equal to 2*artan(x / 2 / y).
[0058] Figure 5 It can be shown that the nitrogen-assisted femtosecond laser processing method is suitable for large-area aluminum alloy flat blackbody processing. Figure 5 bd is the electron microscope test result of the black body. It can be seen that the micro-nano composite structure is uniform, the top is a cone tip, and it has a high aspect ratio. Figure 5 E and Figure 5 f is the corresponding three-dimensional confocal test result, which can more intuitively observe the uniformity of the structural morphology. Figure 5 g is the test result of light absorption rate in the range of 200nm-25μm. It can be seen that the absorption rate is very uniform in the whole test range, and achieves a high absorption rate of more than 98.5%. The test result of this ultra-wide spectrum high absorption rate is at the international leading level.
[0059] Example 2
[0060] This embodiment provides a method for preparing cone-shaped micro-nano composite structures of different periods and depths by using nitrogen-assisted femtosecond laser processing. The specific preparation process is the same as that of Example 1, except that the background gas is changed to argon and an absorption rate test is performed.
[0061] Under the same laser processing parameters and gas flow rate, that is, only the type of background gas is changed, the absorptivity of the aluminum alloy plane black body prepared in three background gas environments of air, nitrogen and argon is tested. Figure 6 As shown, it can be seen that the absorption rate curve obtained in the air environment is lower in the near-infrared region and higher in the mid-wave infrared to long-wave infrared region. In the nitrogen and argon environments, the absorption rate curve obtained is relatively uniform in the entire test range due to the suppression of the plasma shielding effect, but the absorption rate curve in the nitrogen environment is significantly higher than that in the argon environment, which verifies that nitrogen-assisted femtosecond laser processing has a better light absorption effect.
[0062] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0063] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0064] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing an ultra-wide spectrum and ultra-high absorption aluminum alloy planar black body using an inert gas-assisted femtosecond laser, characterized in that: The specific steps include: Step 1: Processing of samples to be processed; The aluminum alloy sample to be processed is placed in a sealed polytetrafluoroethylene beaker with acetone solution, taken out after ultrasonic cleaning, rinsed with ethanol and deionized water in turn, and placed in a low-temperature oven for drying; then the aluminum alloy sample is taken out for use, and the sample preparation is completed; Step 2: Processing aluminum alloy samples by femtosecond laser in an inert gas environment; First, the sample is placed in a transparent box that can pass inert gas. The box is fixed on a two-dimensional mobile platform to meet the precise movement of the sample in the XY plane. The femtosecond laser emitted by the femtosecond laser enters the three-dimensional galvanometer processing system focused by the field lens after beam expansion. The galvanometer of the three-dimensional galvanometer processing system is installed on a z-axis displacement stage that can move up and down. The femtosecond laser deflected by the galvanometer is then focused on the upper surface of the sample through the field lens. Then, the switch of the gas cylinder containing inert gas is turned on to pass inert gas into the transparent box. Finally, the z-axis is adjusted to make the laser focus on the upper surface of the sample, and the pre-designed processing file is read into the processing program. The direct writing processing is performed by scanning back and forth row by row on the x-axis and then scanning back and forth column by column on the y-axis. Finally, a conical micro-nano composite structure with a high aspect ratio can be prepared. Step 3: ultrasonic treatment of metal samples; The sample obtained in step 2 is ultrasonically cleaned to remove the debris remaining after processing and retain the stable cone-shaped micro-nano composite structure. It is then dried in a dryer or blown dry with an ear bulb. At this point, the aluminum alloy sample with ultra-wide spectrum and ultra-high absorption rate is prepared.
2. The method for preparing an ultra-wide spectrum and ultra-high absorption aluminum alloy planar blackbody using an inert gas-assisted femtosecond laser as claimed in claim 1, characterized in that: In step 1, the size of the aluminum alloy sample to be processed is 3 cm-10 cm, the thickness is 1 mm-10 mm, the ultrasonic time is 0.1 h-2 h, and the temperature of the low-temperature oven is set to 50° C.-100° C.
3. The method for preparing an ultra-wide spectrum and ultra-high absorption aluminum alloy planar blackbody using an inert gas-assisted femtosecond laser as claimed in claim 1, characterized in that: In step 2, there is a circular hole on each of the left and right sides of the transparent box, which is connected to an external gas pipe for the inert gas to flow in and out, and the flow rate of the inert gas is 0.1-10L / min.
4. The method for preparing an ultra-wide spectrum and ultra-high absorption aluminum alloy planar blackbody using an inert gas-assisted femtosecond laser as claimed in claim 1, characterized in that: In step 2, the inert gas is nitrogen or argon.
5. The method for preparing an ultra-wide spectrum and ultra-high absorption aluminum alloy planar blackbody using an inert gas-assisted femtosecond laser as claimed in claim 1, characterized in that: In step 2, the moving range of the x-axis and y-axis of the two-dimensional moving platform is 0-10cm, and the moving range of the z-axis translation stage is 0-10cm, with an accuracy of 1μm; the galvanometer used in the three-dimensional galvanometer processing system is composed of an XY optical scanning head, an electronic drive amplifier and an optical reflective lens. The signal provided by the computer controller is sent to the electronic drive amplifier, which is used to drive the XY optical scanning head, thereby controlling the high-speed deflection of the laser beam in the XY plane, with a moving accuracy of 10-100nm; the laser polarized by the galvanometer is then focused on the sample surface through the field lens to realize femtosecond laser direct writing processing.
6. The method for preparing an ultra-wide spectrum and ultra-high absorption aluminum alloy planar black body using an inert gas-assisted femtosecond laser as claimed in claim 1, characterized in that: In step 2, the fundamental wavelength of the femtosecond laser is 1030nm, and after double frequency the wavelength becomes 515nm, which is a femtosecond laser in the visible region; or after triple frequency, a near-ultraviolet femtosecond laser or nanosecond laser, or picosecond laser of 343nm is obtained; the repetition frequency of the laser is 50kHz-1000kHz, and the pulse width is 280fs; the focal length of the focusing field lens used is 5-20cm, which meets the requirements of large-area processing, and even the objective lens or lens focusing can still prepare the required cone-shaped micro-nano composite structure; the single pulse energy of laser ablation is 1-100μJ, and the laser scanning speed is 1-1000mm / s, which meets the requirements of high-speed processing; the point spacing of the processing data is 50-10000nm, the period is 10-100μm, the layer spacing is 1-30μm, and the number of scans is 1-100 times.
7. The method for preparing an ultra-wide spectrum and ultra-high absorption aluminum alloy planar black body using an inert gas-assisted femtosecond laser as claimed in claim 1, characterized in that: In step three, the ultrasonic cleaning time is 0.1h-2h; the solution used for ultrasonic cleaning is deionized water or ethanol, which can remove debris that is not firmly bonded to the surface of the cone-shaped micro-nano composite structure.
8. An ultra-wide spectrum, ultra-high absorption aluminum alloy flat black body, characterized in that: The aluminum alloy plane black body is prepared by the method described in any one of claims 1 to 7, wherein the anti-reflection structure with adjustable period and aspect ratio is provided on the aluminum alloy plane black body, and the anti-reflection structure is a conical micro-nano composite structure, and the tip angle of the conical micro-nano composite structure is less than 10°.
9. The ultra-wide spectrum, ultra-high absorption aluminum alloy flat black body according to claim 1, characterized in that: The cone-shaped micro-nano composite structure comprises a micron cone-shaped structure layer, an oxide layer and a nano particle layer.
10. The ultra-broad spectrum, ultra-high absorption aluminum alloy flat black body according to claim 1, characterized in that: The cone-shaped micro-nano composite structure can achieve an absorption rate of more than 98.5% within the range of 200nm-25μm.
Citation Information
Patent Citations
Laser modeling method for semiconductor material micro-nano multi-scale function surface
CN101219770A
Femtosecond laser micro / nano fabrication device and method for controlling gas atmosphere
CN102284790A
Laser blackening treatment method for metal surface
CN112756777A
Anti-reflection material manufacturing method and device
CN113732512A
Laser surface blackening method for high-reflectivity metal
CN115415663A